后路腰椎融合内固定术后感染的危险因素分析 (Nan Fang Yi Ke Da Xue Xue Bao, 2018)
OBJECTIVE: To analyze the risk factors of surgical site infection (SSI) following posterior lumbar intervertebral fusion. METHODS: This retrospective case-control study was conducted in 2904 patients undergoing posterior lumbar intervertebral fusion from 2011 to 2016. Forty-three patients with SSI within 30 days after the operation served as the case group, and 334 randomly selected patients without infection served as the control group. Age, gender, diabetes, body mass index (BMI), albumin level, multilevel procedures, subcutaneous fat thickness, surgery duration and the percentage of lumbar multifidus muscle fat infiltration were analyzed, and univariate and multivariate logistic regression analyses were performed to identify the risk factors of SSI. RESULTS: Multivariate logical regression analysis identified a female gender, subcutaneous fat thickness, multilevel surgery, and lumbar multifidus muscle fat infiltration as significant risk factors for SSI (P < 0.05). BMI was not correlated with fat infiltration in the lumbar multifidus muscle (P > 0.05). CONCLUSION: A female gender, multilevel surgery, subcutaneous fat thickness and fat infiltration in the multifidus muscle are related to SSI following posterior lumbar intervertebral fusion. Fat infiltration in the multifidus muscle was a spine-specific risk factor for SSI independent of BMI.